Лечебная физическая культура в теории и практике: учебное пособие - Капилевич Л. В. Леонид Владимирович; Давлетьярова К. В. Ксения Валентиновна; Баранова Е. А. Елена Алексеевна; Бредихина Ю. П. Юлия Петровна; Андреев В. И. Владимир Игоревич (Томск, Изд-во ТПУ, 2022)
Заглавие с титульного экрана